JMP Volume VII No 1 Edisi Desember 2017 - Redaksi JMP (Jurnal Maksipreneur, 2017)
Entering the seventh year, JMP returned to present featuring seven articles from competent researchers and writers. JMP is opened with Prasetyo and Arsanti research article that reveals about various factors that influence the students to be involved or not involved in a discussion. Furthermore, Hidayati and Ermiyanto reveal the results of their research in the field of human resources about intrinsic and extrinsic motivation, as well as job satisfaction and employee performance in an organization, while Purwanto reveals the characteristics of agate collector accompanied by an explanation on the purchase process. In their research, Purnomo and Purnomo found a very important role of teachers in growing entrepreneurial intentions, especially for deaf students. Next, Mahsina, Poniwatie, and Cholifah present the results of qualitative research and explain the application of the balanced scorecard as an agency's performance benchmarks. In its conceptual thinking, Risdwiyanto describes a high performing organization as a way or a solute approach for the organization in dealing with the turbulence of the business environment. As the end of the dish, Sukrajap and Harahap reveal their research results about the impact of self-leadership training and achievement motivation for the Village Head.